Search Costs, Information Exchange and Sales Concentration in the Digital Music Industry - Néstor Duch-Brown; Bertin Martens (European Commission, Joint Research Centre (JRC), 2014)
It is often assumed that consumers benefit from the internet because it offers a “long tail” with more variety of products to choose from. However, search costs may block the long tail effect and result in the dominance of superstars. This paper examines the variety hypothesis in the entire online market for digital music downloads in 17 countries over the period 2006-2011. First, we show that the entire distribution of legal music downloads is heavily skewed. Second, we hypothesise that a wide range of online information channels (sales and discovery platforms) play a role in this market. We find that the reduction of search costs implied by the generalisation of online information tools transforms demand as a result of changes in the dispersion of preferences. Ubiquitous and very popular discovery channels such as Facebook and iTunes tend to push consumers towards the superstars by shifting the demand curve but also towards the long-tail since they also generate rotations that promote niches. Conssequently, both the superstar and the long tail effects emerge even in mature digital markets.
Keywords: C46; D12; L82; 330; digital markets; search costs; information; sales concentration; online markets